2016
DOI: 10.1080/20477724.2016.1173325
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmosis awareness, seroprevalence and risk behavior among pregnant women in the Gampaha district, Sri Lanka

Abstract: Health education programs to increase awareness of toxoplasmosis is recommended at antenatal clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Over the past five years there has been a significant decrease of toxoplasmosis among pregnant women. Similar results were described by Chandrasena et al (2016). In a study conducted in Saudi Arabia by Elsafi et al, (2015), the seroprevalence of toxoplasma among pregnant women were 28% and 3% for IgG and IgM respectively while more than 75% of the women were unaware of the disease toxoplasmosis.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Over the past five years there has been a significant decrease of toxoplasmosis among pregnant women. Similar results were described by Chandrasena et al (2016). In a study conducted in Saudi Arabia by Elsafi et al, (2015), the seroprevalence of toxoplasma among pregnant women were 28% and 3% for IgG and IgM respectively while more than 75% of the women were unaware of the disease toxoplasmosis.…”
Section: Discussionsupporting
confidence: 70%
“…This is to show that most of the patients, who had past infection, probably did not get it from the animals, but about 40% of these antibodies were found in patients who had dogs, which might serve as one of the potential risks for toxoplasmosis. Similarly, a study in Sri Lanka indicated that animal ownership did not have a significant impact on the seroprevalence of Toxoplasma (Chandrasena et al, 2016). In a study in Spain, Cano-Terriza et al (2016) found a high prevalence of Toxoplasma IgG in dogs and the prevalence was associated with the age of the dogs.…”
Section: Discussionmentioning
confidence: 95%
“…However, higher seroprevalence were reported in other countries such as Brazil (71%), Lebanon (82.6%), Ethiopia (85.3%), and Ghana (92.5%) [3639]. In contrast, lower seroprevalence of T. gondii infection were reported in Zambia (5.9%), Mexico (8.2%), Sri Lanka (12.3%) and in many European countries [2, 4042]. This variation in the seroprevalence of T. gondii infection is observed worldwide and it has been attributed to various determinants such as the use of diagnostic methods of different sensitivity, and the limitations of the surveys in controlling the differences between cohorts [43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…In Sri Lanka, T. gondii awareness among pregnant women equaled only 4.4%. Health personnel and media were the sources of information in 46.2% and 53.8%, respectively [ 15 ]. Likewise, it was reported that 3/4 of 400 pregnant Saudi women had never heard of toxoplasmosis, and those who lacked that knowledge were at 4.04 times higher risk of toxoplasmosis [ 16 ].…”
Section: Discussionmentioning
confidence: 99%